Model of leakages through radial clearences in a single screw extruder with linearly changing geometry of screw - Petrov, Iliya Andreevich; Slavnov, Evgeniy Vladimirovich (Computational Continuum Mechanics, 2012)
The model of mass transfer of fluid flow through the radial clearance between the inner surface of the extruder barrel and screw with linearly varying geometry is proposed. It is assumed that the leakage of fluid over the flight changes the flow rate along the screw conduit, which specifies pressure gradient. The pressure gradient defines in turn the rate of leakages, and hence the flow of leakages is considered as a distributed feedback. The system of equations is solved using the method of successive iterations for cylindrical screws, conic screws and screws with a changing pitch. The influence of the clearance height on the pressure drop – flow rate characteristics of the screw and the type of pressure distribution is analyzed.
Keywords: flow in extruder; radial leakages; circulation; distributed feedback; argument deviation